THE SOCIAL AND ECONOMIC CONCATENATION IN THE TOURISM OF MOZAMBIQUE - Charomar, Joao Antonio (PEOPLE: International Journal of Social Sciences, 2019)
Our analysis of the social and economic relationship in the tourism of Mozambique besides our personal relationship was motivated by the exploration of the potential hidden in the tourism targeting developing countries. In the analysed country the percentage contribution of travel-tourism sector to the overall GDP from 2008 to 2018 started to increase again after plummeting during 2011 and 2012 but has stagnated since 2015. In the medium term the sector output has been increasing continually since 2008 except for the period 2011-2012 (2017: 455.9 million USD) and according to the data revealed by WTTC in 2018 it is expected to increase 1.5 times. However, the 2017 figure places the country in the 136th position in the world ranking lagging well behind the world average (21.5 billion USD). In our research we analyse the social and economic causes of the country’s small competitiveness. We also unfold the tourism supply elements, the role played by the sector in the economy of Mozambique. We sought answer to the question whether the society sees opportunities for engaging efficiently in tourism and what experiences it has had in the process of welcoming tourists. In answering the economic questions we have compared secondary data and information. In our primary research we have prepared a questionnaire for ordinary citizens and institutions operating in the tourism sector. In these questions we have asked their opinions, attitude, formal education level and their willingness to engage in tourism in the future. We believe these two themes are crucial for boosting tourism in the country. This research, as the first step, also aims to build an international research relationship in the future.